Um estudo da melancolia na poesia lírica de Joaquim Cardozo - Silva, Robson Nascimento da (2021)
This work aims to analyze some poems in Joaquim Cardozo’s poetic work published as of 1970, i.e, his last lyrical writings, which indicate the presence of a melancholic discourse in his lyrical I, and how such questions help to enlighten his formulations. Thus, this investigation raises the following question: how does melancholy become one of the central keys to the Cardozian lyrical I’s constitution, and which historic and aesthetical issues shaped this proposition? For this, the hypotheses that guide this work are 1. The melancholic tone in Cardozo’s poetry induces a reading that, in turn, reinforces the understanding of a subject disarticulated with the surrounding spaces; 2. The aesthetic procedures used by Cardozo to compose some of his poems support the reading of a lyrical I that turns against and about itself in a melancholic perspective; 3. Melancholy will be perceived around some poetic forms, like the sonnet, the elegy, and the song as a part associated with its composition, modulating new perspectives to these traditional forms. Therefore, in the analytical chapters, we will more specifically delimit the main aesthetic developments of melancholy in the Cardozian poetry, to discuss how it occurs and, therefore, why they are recurrent in his works. For this purpose, o theoretical framework collected for this research focuses, above all, on the studies on melancholy, by Jean Starobinski (2011; 2016), Freud (1992), Lambotte (2000), Löwy and Sayre (2015), and Lima (2017).